The Franciscans and the Independence of Chile: The voices and actions of the seraphic friars - Leal Pino, Cristián (2020)
The article analyzes the Franciscan Order of Chile in the independence period, focusing on two units: the Province of the Holy Trinity and the Chillan Mission College. First, we offer a look from historiography and then give way to the voices and actions of some religious in the independence process. The Order had to collaborate with the civil authorities in a climate of war, with either economic donations or facilitating their dependencies to the army. However, another thing is to observe its position in the face of events and the way they channeled it. For this, we have consulted historical documents of the period, emanated from the friars themselves, such as patent letters, letters, circulars, and press writings. Through critical reading and triangulation, we have been able to reach conclusions. In this sense, we can affirm that the voices and actions of the friars were changing, depending a lot on the course of events. The bulk of them was oblivious to the process, living the internal issues that had afflicted them since the last century, in terms of the relaxation of customs and life in common.